2016
DOI: 10.1111/epi.13342
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal cognitive network interactions in Lennox‐Gastaut syndrome: A potential mechanism of epileptic encephalopathy

Abstract: SUMMARYObjective: In patients with Lennox-Gastaut syndrome (LGS), recurrent epileptic activity is thought to contribute to impaired cognition (epileptic encephalopathy). Using concurrent electroencephalography-functional magnetic resonance imaging (EEG-fMRI), we recently showed that epileptiform discharges in LGS recruit largescale networks that normally support key cognitive processes. In LGS, given that epileptic activity engages cognitive networks, and cognition is pervasively impaired, we hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…We previously found that widespread areas of the executive‐control and default‐mode networks are recruited during tonic seizures and epileptiform discharges in LGS. Additionally, LGS patients show abnormal functional connectivity within the default‐mode network, and between the default‐mode and executive‐control networks . Considered together, these results raise the hypothesis that the expression of epileptic activity in thalamus–executive‐control and thalamus–default‐mode circuits disrupts normal connectivity, potentially contributing to impaired cognition in LGS.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…We previously found that widespread areas of the executive‐control and default‐mode networks are recruited during tonic seizures and epileptiform discharges in LGS. Additionally, LGS patients show abnormal functional connectivity within the default‐mode network, and between the default‐mode and executive‐control networks . Considered together, these results raise the hypothesis that the expression of epileptic activity in thalamus–executive‐control and thalamus–default‐mode circuits disrupts normal connectivity, potentially contributing to impaired cognition in LGS.…”
Section: Discussionmentioning
confidence: 87%
“…Task‐free fMRI data were acquired as part of a larger multisite study of LGS . All subjects were scanned using T 2 *‐weighted gradient‐recalled echo‐planar image sequences (for detailed acquisition parameters, refer to Methods ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased rate of epileptiform discharges has been associated with lower performance on cognitive functioning and attention-sensitive tasks [Kasteleijn-Nolst et al, 1987, 1988Ebus et al, 2012;Nicolai et al, 2012], which is dependent on when and where the activity occurs [Kleen et al, 2013]. Non-transient effects of IEDs are less well characterised although there is some evidence that a worse cognitive outcome in the long term is related to increased frequency of epileptic discharges in focal epilepsies [S anchez Fern andez et al, 2015] and at onset of Lennox-Gastaut syndrome [Warren et al, 2016].…”
Section: Introductionmentioning
confidence: 99%